2020
DOI: 10.3389/fimmu.2020.587913
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Suppresses Macrophage Pro-Inflammatory Response to LPS Stimulation by Inhibition of YAP and NF-κB Activation via GPR81-Mediated Signaling

Abstract: Recent evidence from cancer research indicates that lactate exerts a suppressive effect on innate immune responses in cancer. This study investigated the mechanisms by which lactate suppresses macrophage pro-inflammatory responses. Macrophages [Raw 264.7 and bone marrow derived macrophages (BMDMs)] were treated with LPS in the presence or absence of lactate. Pro-inflammatory cytokines, NF-κB and YAP activation and nuclear translocation were examined. Our results show that lactate significantly attenuates LPS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
106
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 54 publications
11
106
1
Order By: Relevance
“…These findings suggested that GPR81 had a potential protective effect on atherosclerosis and targeting GPR81 may inhibit OSS-induced endothelial inflammation and dysfunction [99]. In 2020, KunYang discovered a new mechanism, found that lactic acid inhibited the activation of YAP and NF-κB during inflammation through GPR81-mediated signal transduction, and inhibited the pro-inflammatory response of macrophages stimulated by LPS [89].…”
Section: Effects Of Lactic Acid Signaling On Inflammatory Responsementioning
confidence: 97%
See 1 more Smart Citation
“…These findings suggested that GPR81 had a potential protective effect on atherosclerosis and targeting GPR81 may inhibit OSS-induced endothelial inflammation and dysfunction [99]. In 2020, KunYang discovered a new mechanism, found that lactic acid inhibited the activation of YAP and NF-κB during inflammation through GPR81-mediated signal transduction, and inhibited the pro-inflammatory response of macrophages stimulated by LPS [89].…”
Section: Effects Of Lactic Acid Signaling On Inflammatory Responsementioning
confidence: 97%
“…The concentration of physiological lactic acid is approximately 1.5-3mM, inncreasing to 10 mM in blood and healthy tissues, and reaching as high as 25 mM after strenuous exercise. In inflammatory diseases, such as atherosclerotic plaques or rheumatic synovial fluid, the concentration of lactic acid can be around 10 mM, and in cancer tissues it can even reach to 20-40mM [19,89]. The accumulation of lactic acid had a great impact on the macrophages that had infiltrated and were staying in the tissue, which fur ther inf luenced disease progression.…”
Section: Effect Of Lactic Acid On Macrophage Polarizationmentioning
confidence: 99%
“…The endogenously produced lactate in the established tumors has been identified as a driver of angiogenesis, immune evasion, metastasis, and resistance to therapy [ 106 ]. On the other hand, lactate delivered by postbiotic supplementation may serve as an inhibitor of carcinogenesis through the maintenance of the epithelial integrity and downregulation of the tissue inflammation [ 11 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Lactic Acidmentioning
confidence: 99%
“…In our study, the biofilm CM of SA and SE contained high amounts of bacterial lactate. In general, extracellular lactate is associated with an inhibitory effect on the pro-inflammatory immune response of macrophages (44)(45)(46). In a recent study, the group of Tammy Kielian compared the effects of biofilm environments from wild-type and a mutant SA strain deficient in the production of Land D-lactate on IL-10 induction (47).…”
Section: Discussionmentioning
confidence: 99%